Implementasi Digital Signage Menggunakan Raspberry Pi - Alvin Nathaniel Santoso; Silvia Rostianingsih; Justinus Andjarwirawan (Jurnal Infra, 2019)
Digital Signage is a form of information delivery through electronic display media (dynamic). So far, digital signage does not provide features next, previous, like and dislike. So people can not give feedback or have to wait for information to read. In today's digital signage placement we can not tell if many people are reading digital signage.To answer the problem, designed digital signage that gives the feature next, previous, like and dislike. By utilizing computer raspberry pi and camera we can know if many see digital signage. This can allow helping to place digital signage in a crowded place and many people are watching and reading. So that the spread of information can spread to the fullest.This application uses open cv as a library and uses the haar cascade method. This application can not detect people 100% due to several factors such as non-bright light, other obstructing objects, faces that do not look full to the camera or digital signage. If the same person keeps reading when the camera takes a picture the person will still be counted.